Feto-maternal Outcomes in Placenta Previa with and Without Previous Cesarean Section - Pun, Isha; Singh, Alka (Journal of Nepal Health Research Council, 2022)
Background: Placenta previa is associated with poor maternal and fetal outcomes. Its complications are increasing due to the increased rate of cesarean deliveries. This study aimed to compare maternal and fetal outcomes in placenta previa with and without previous cesarean section. Methods: This study was conducted in the Department of Obstetrics and Gynecology at Patan Hospital, Nepal. Placenta previa cases were reviewed from 1st January 2010 to 31st December 2019, parted into Group 1 (placenta previa with previous cesarean section) and Group 2 (placenta previa with no prior cesarean section). Strength of association was measured as odds ratio and 95% confidence intervals. P-value at <0.05 was taken as statistically significant. Results: The total number of placenta previa were 348 (0.42%) of total deliveries (n=82,918) , but 72 charts/records were not found and six cases were excluded. Group 1 comprised 48 cases (0.86%) among prior cesarean section (n=5,581) and Group 2 consisted of 222 cases (0.28%) among those with no prior cesarean delivery (n=77,337) and it was statistically significant. Morbidly adherent placenta, postpartum hemorrhage, cesarean hysterectomy, and maternal deaths were higher in Group 1 and statistically significant. Preterm deliveries and neonatal intensive care unit admission were also more in Group 1 and statistically significant. Conclusions: Maternal and fetal morbidity were higher in placenta previa with previous cesarean section than with no prior cesarean delivery. Therefore, it is advisable to try to reduce the rate of cesarean section as far as possible. Keywords: Feto-maternal outcome; placenta previa; previous cesarean section.